O obecności literatury polskiej w Czechach i czeskiej w Polsce. Komentarz do bibliografii przekładów w roku 2018 - Żygadło-Czopnik, Dorota (Przekłady Literatur Słowiańskich, 2020)
In this commentary, we will limit ourselves to presenting the reception of Czech literature in Poland and Polish literature in the Czech Republic in the year 2018. Czech and Polish literature reaches its readers across their respective borders in several ways: via translations of books by well-known and esteemed writers; through representatives of the younger generation; and as translations of prose and poetry published in magazines. The reception of Polish and Czech literature has been very positive; specifically, there is a growing interest among Polish readers in Czech literary offerings.